Incentive Effects and Gender-Based Outcome Differences in Hierarchical Promotion Systems - Seymour, Richard George (Curtin University, 2015)
The thesis examines gender differences in the promotion of academics within the Australian university sector. The analysis uses data from Curtin University, which is a large representative university within the sector, to examine the determinants of promotion probabilities at the University during the period 1998 and 2004. One key finding from the thesis is that female academics were less likely to be promoted from the levels of lecturer and senior lecturer during the study period.